Methodological features of the development of the communicative competence of local general practitioner in preventive counseling - S. Yu. Astanina; A. M. Kalinina; R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
There is a contradiction between the need of teachers of internal medicine departments in the methodology for communicative competence (CC) of general practitioners in brief preventive counseling and the lack of evidence-based classes on CC formation in brief preventive counseling.The existing contradiction made it possible to identify the research problem — the need to develop a methodology for the development of CC of general practitioners in brief preventive counseling.In the context of the problem, the study aim was determined — to define the methodological features of CC formation in the general practitioner in brief preventive counseling.To achieve this goal, the following research methods were used: theoretical: theoretical analysis of philosophical, pedagogical, psychological and methodological literature; designing the educational process; experimental: direct and indirect pedagogical observation, pedagogical experiment, questioning, control sections.The methodological features of CC formation are the simultaneous development of the intellectual and emotional fields of the doctor’s personality (communication skills in conducting all stages of brief preventive counseling) and the volitional field of the doctor’s personality (belief in the need to master the CC of doctor-patient interaction).The method of doctor’s CC development is based on the technology of educational training. The content of the training is a system of three following components: cognitive component — knowledge of the regulatory framework for conducting brief preventive counseling; knowledge about the criteria for its effectiveness; features of the management and principles of implementation; emotional and motivational component — the formation of personally significant ideas about oneself as a subject of professional communication in the process of brief preventive counseling; the behavioral component is the formation of the doctor’s beliefs in the need to master communicative skills that ensure the formation of competence in brief preventive counseling.The results of its experimental implementation for the formation of a doctor CC showed a high level of development: skills in conducting all stages of brief preventive counseling; beliefs in the need for the doctor to master the CC of doctor-patient interaction.